2007
DOI: 10.1089/acm.2006.6128
|View full text |Cite
|
Sign up to set email alerts
|

Miniscalpel-Needle Versus Triggerpoint Injection for Cervical Myofascial Pain Syndrome: A Randomized Comparative Trial

Abstract: Dear Editor:Whether or not acupuncture intervention involves neurologic effects has recently been explored via functional magnetic resonance imaging (fMRI) experiments commonly consisting of multiple experimental blocks with ON-and OFF-condition alternations. Such fMRI experiments normally employed a block interval of more than a minute. 1-3 However, the psychophysical response to acupuncture, a needling (or de qi) sensation (a sensation including sourness, numbness, heaviness, and distension surrounding the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…47 On the other hand, MSN release technique has the effects of acupuncture, including stimulation of vessel and nerve bundles, restoration of the mechanical dynamic equilibrium, and improvement of local microcirculation. Wang et al 39 reported that there was a significant improvement in PI, contralateral bending ROM of the cervical spine, and the neck pain and disability after MSN release treatment, and the improvement was significantly greater than that of 0.25% lidocaine TrPs injection. 39 In our study, PI, PPT, and contralateral bending ROM of the cervical spine in MSN release group were significantly improved at 2 weeks and 3 months follow-up, compared with acupuncture needling treatment group and self neck-stretching exercise group.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…47 On the other hand, MSN release technique has the effects of acupuncture, including stimulation of vessel and nerve bundles, restoration of the mechanical dynamic equilibrium, and improvement of local microcirculation. Wang et al 39 reported that there was a significant improvement in PI, contralateral bending ROM of the cervical spine, and the neck pain and disability after MSN release treatment, and the improvement was significantly greater than that of 0.25% lidocaine TrPs injection. 39 In our study, PI, PPT, and contralateral bending ROM of the cervical spine in MSN release group were significantly improved at 2 weeks and 3 months follow-up, compared with acupuncture needling treatment group and self neck-stretching exercise group.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al 39 reported that there was a significant improvement in PI, contralateral bending ROM of the cervical spine, and the neck pain and disability after MSN release treatment, and the improvement was significantly greater than that of 0.25% lidocaine TrPs injection. 39 In our study, PI, PPT, and contralateral bending ROM of the cervical spine in MSN release group were significantly improved at 2 weeks and 3 months follow-up, compared with acupuncture needling treatment group and self neck-stretching exercise group. However, in clinical practice TrP injections are usually conducted with both steroid and local anesthetics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations